Study of organic semiconductor based photovoltaic devices: light sensors and solar cells / Karwan Wasman Qadir - Karwan Wasman, Qadir (2016)
Recently, organic photovoltaic devices (OPVDs) have been extensively studied and demonstrated as promising candidates for light sensing applications. The novel materials are used in optoelectronic applications, utilizing their intrinsic physical, chemical and electrical characteristics. Organic semiconductors offer many physical and chemical properties that can be easily tailored by incorporating functional groups or manipulating physical conditions to meet specific requirements. The best feature of organic semiconductors is their solution processability at room temperature using simple and low cost deposition techniques. Aiming at the interesting properties of organic semiconductors, in this thesis, we have extensively explored organic semiconductors based solar cells and light sensors for optoelectronic applications. Dye sensitized photo sensors using water soluble organic photo sensitizer, Nickel (II) phthalocyanine-tetrasulfonic acid tetrasodium salt (NiTsPc) have been fabricated and investigated. Two different types of TiO2 films (untreated and NaOH-treated) are prepared to serve as anodes for the sensors. Both films are subsequently sensitized by NiTsPc using aqueous solution. Commercially available Iodolyte Z100 and platinum coated indium doped tin oxide (ITO) are used as electrolyte and cathode, respectively. The NaOH-treated sensor demonstrates 2.81 times increase in sensitivity in terms of photo-conductivity as compared to the untreated sensor. The NaOH-treated sensor, however, surpasses the other sensor in terms of response/recovery times and stability in plateau values of the photocurrent. The proposed photosensor is eco-friendly and economical for commercial applications. A binary blend of two polymers, poly[2,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta [2,1-b;3,4-b’]dithiophene)-alt-4,7(2,1,3-benzothiadiazole)] (PCPDTBT) and poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] (MEH-PPV) as a sensitizer has been employed for a visible light dye sensitized photo sensor (DSPS). The proposed combination of the polymers covers almost the entire visible light spectrum. iv The dependence of the current generation in the dye sensitized photo sensor is investigated as a function of varied incident light intensities. The output shows a linear relation as a function of incident light in the range of 0-30000 lx. The photo-conductivity sensitivity of the dye sensitized photo sensor is about 2.02×10−5 Sm/W. The average response time of the sensor is found ∼382 ms. In addition to consistency and repeatability, the fabrication of this sensor is economical and environmentally friendly. The effect of thermal annealing on the optical, morphological and photovoltaic properties of bulk heterojunction solar cell based on the poly[2,5-bis(3-dodecylthiophen-2-yl)thieno[3,2-b]thiophene] (PBTTT-C12) and[6,6]-phenyl C71-butyric acid methyl ester (PC71BM) has been investigated. The ITO/PEDOT:PSS/PBTTT-C12:PC71BM/Al devices are fabricated on glass substrates from the PBTTT-C12:PC71BM (1:4) solution in dichlorobenzene. Atomic Force Microscopy (AFM) is used to investigate the surface morphology of the PBTTT-C12:PC71BM thin films. The AFM results show that the surface roughness of the thin film decreases with increasing annealing temperature, making the annealed film smoother as compared to the non-annealed sample. The efficiency of the ITO/PEDOT:PSS/PBTTT-C12:PC71BM/Al photovoltaic devices increases from 1.85 to 2.48% with an increment in the temperature ranging from 0 ℃ to 150 ℃.